PEMBERDAYAAN PEMUDA DALAM GERAKAN PEDULI LINGKUNGAN MELALUI LITERASI SASTRA HIJAU (GREEN LITERATURE) DI DUSUN III DESA TANJUNG GUSTA, KECAMATAN SUNGGAL - Fardian Gafari, M. Oky; Chairunnisa, Hera; Arianto, Tomi; Fahmy Dalimunthe, Syairal; Kurnia Pulungan, Hendra; Reviani Manullang, Ester; Damanik, Bea Anantha; Septiani Sihaloho, Jelita (ASOSIASI IDEBAHASA KEPRI, 2025)
The city of Medan is facing a critical environmental situation due to recurrent flooding that has affected various areas throughout 2024–2025. According to data from the Regional Disaster Management Agency (BPBD) of Medan, there are 25 flood-prone points, with 7,699 houses inundated and 24,874 residents affected. This condition is exacerbated by the low level of public awareness regarding environmental cleanliness and unplanned urban development that neglects ecological balance. In response, a community service team from the Department of Indonesian Literature conducted a program entitled “Environmental Awareness Movement through Green Literature” in Dusun III, Tanjung Gusta Village, Sunggal Subdistrict—one of the flood-prone areas in Medan. The program involved approximately 50 young participants and featured two expert speakers: an ecologist and a literary scholar specializing in environmental studies. Participants showed strong enthusiasm throughout the sessions, which included lectures, group discussions, and interactive question-and-answer activities. The materials covered topics such as ecosystem preservation, the impact of waste on water channels, and the role of literature as an educational and inspirational medium for fostering environmental awareness. As a follow-up, participants and the community service team initiated concrete actions such as tree planting, community clean-up activities, and the creation of eco-literary works, including poetry and short stories with ecological themes. The program not only encouraged behavioral change toward environmental stewardship but also aimed to develop youth as role models for environmentally conscious communities. The program outputs include a submitted national journal article, online news coverage, a training module (in progress for ISBN registration), an intellectual property (HAKI) submission, and a documentary video—serving as tangible contributions to environmental sustainability in Medan.